27. Educational Wikis: Features and selection criteria - Schwartz, Linda; Clark, Sharon; Cossarin, Mary; Rudolph, Jim (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
This report discusses the educational uses of the ‘wiki,’ an increasingly popular approach to online community development. Wikis are defined and compared with ‘blogging’ methods; characteristics of major wiki engines are described; and wiki features and selection criteria are examined.